Prevalence and incidence of injuries in para athletes: a systematic review with meta-analysis and GRADE recommendations - Santos Pinto Pinheiro, L.; Melo Ocarino, J.; Oliveira Madaleno, F.; Verhagen, E.; Túlio de Mello, M.; Rodrigues Albuquerque, M.; Pereira Andrade, A. G.; da Mata, C. P.; Zambelli Pinto, R.; Silva, A.; Alves Resende, R. (British Journal of Sports Medicine, 2021)
Objective: To investigate prevalence, incidence and profile of musculoskeletal injuries in para athletes.